THE ROLE OF SILICA NANOPARTICLES IN MODULATING GROWTH PERFORMANCE, ENZYME ACTIVITY, AND HEAVY METAL ACCUMULATION IN MUSCLE TISSUE OF COMMON CARP (Cyprinus carpio. L) - Owais, Muhammad; Mohammed, Dilsher Ahmed; Mhammad, Husni A; Al Sulivany, Basim S A; Dernekbaşı, Seval; Fazal, Rana Meroz (Science Journal of University of Zakho, 2025)
This study investigated the effects of dietary supplementation with silicon nanoparticles (Si-NPs) on the growth performance, trace element concentrations, and serum enzyme activity of Cyprinus carpio (C. carpio) over a 90-day feeding trial. Four experimental diets with varying levels of Si-NPs were prepared: the first group (GRP1) was given 0 mg/kg, the second group (GRP2) received 1 mg/kg, the third group (GRP3) was supplemented with 2 mg/kg, and the fourth group (GRP4) had 3 mg/kg of Si-NPs. Results revealed that moderate levels of Si-NPs (1-2 mg/kg) significantly improved growth performance (p < 0.05), with GRP3 exhibiting the highest final weight (35 ± 0.44 g), weight gain (22.4 ± 0.5 g), and feed conversion ratio (1.269 ± 0.023). In contrast, GRP4 (3 mg/kg) showed reduced growth. Trace element analysis demonstrated that Si-NPs at 1-2 mg/kg enhanced the bioavailability of essential elements such as Sodium (Na), Iron (Fe), Magnesium (Mg), and Zinc (Zn), while higher doses disrupted trace element homeostasis. Serum enzyme activities, including Alanine Aminotransferase (ALT), Aspartate Aminotransferase (AST), Acid Phosphatase (ACP), Alkaline Phosphatase (ALP), and Lactate Dehydrogenase (LDH), were significantly reduced in GRP2 and GRP3, suggesting a protective effect against oxidative stress and tissue damage. However, enzyme activities of GRP4 returned to control values, implying a threshold effect. The research indicates the beneficial effect of Si-NPs as a food supplement for growth enhancement, nutrient assimilation, and protecting the fish against oxidative stress if dosing is carefully adjusted to avoid toxicity.